IBM Cognos TM1 developer's certification guide : fast track your way to COG-310 certification! - Miller, James D. (Software consultant) (Professional expertise distilled., 2012)
This book is packed with real word examples. Each major certification topic is covered in a separate chapter, which helps to make understanding of concepts easier. At the end of each chapter, you will find a variety of practice questions to strengthen and test your learning. If you are a beginner to intermediate level Cognos TM1 developer looking to add an important IBM certification to your resume but don't know where to start, this book is for you!